Analisis Pemahaman Konsep Matematika Siswa Kelas VII pada Operasi Hitung Bilangan Bulat - Nurhaliza, Saripa; Anggraini, Anggraini; Mustamin Idris; Gandung Sugit (Jurnal Pendidikan Matematika : Judika Education, 2025)
The purpose of this study was to obtain a description of the Analysis of Students' Mathematical Concept Understanding of Grade VII SMP Negeri 3 Ampibabo in Integer Arithmetic Operations who have high, medium, and low mathematical abilities in solving integer arithmetic operations problems. This type of research is qualitative research. The subjects in this study were 3 students taken from 20 grade VII students of SMP Negeri 3 Ampibabo in the odd semester of 2024/2025. Subjects were selected based on test scores and subject teacher recommendations. Data were obtained from the results of written tests and interviews with research subjects. The results showed that subjects with high abilities could meet 3 indicators, namely restating concepts, Classifying objects according to certain properties, and Presenting concepts in various forms of mathematical representation. Subjects with medium abilities could meet 2 indicators, namely restating concepts, and Presenting concepts in various forms of mathematical representation. Subjects with low mathematical abilities only met 1 indicator, namely restating concepts. Thus, it can be concluded that the level of students' mathematical concept understanding of integer arithmetic operations varies depending on their mathematical abilities. Students with higher mathematical abilities demonstrate better and more comprehensive understanding of concepts.   Keywords: Analysis, Conceptual Understanding, Integer Arithmetic Operations, Mathematical Ability.